PENGARUH PERTUMBUHAN PERUSAHAAN, RASIO KEUANGAN, DAN KUALITAS AUDITOR TERHADAP OPINI AUDIT GOING CONCERN - Sesty Farica Purba; Nazmel Nazir (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
The purpose of this research is to analyze the effect of company growth on going concern audit opinion, the effect of company size on going concern audit opinion, the effect of liquidity on going concern audit opinion, the effect of solvability on going concern audit opinion, profitability, and the effect of quality auditor on going concern audit opinion. The research was causal comparative research. The sample used in this research were manufacturing companies listed in Indonesian Stock Exchange in 2014-2017. Those companies were selected by purposive sample method. There were 101 companies. The data were tested by logistic regression analysis. The results showed that solvability was significantly influenced the acceptance going concern audit opinion. In contrast, company growth, company size, profitability, liquidity, and quality auditor were not have any significant influence to the acceptance going concern adit opinion.